THE USE OF ROLE PLAY TO IMPROVE SPEAKING SKILL AT EIGHTH GRADE STUDENTS OF SMP NEGERI 2 SIBORONGBORONG - Rekolina Siahaan; Mariati Saragih (Journal of Innovative and Creativity, 2026)
This Research about the improvement of students’ achievement in speaking for the eighth grade students in SMP Negeri 2 Siborongborong by using Role Play. Role Play is the method that helps the teacher to relate between the materials with the real situation and invited the students to make a relation between their knowledge with how to do it in their lives. Role Play has positive effect to improve students’ skill in speaking and make students more active and know the meaning of what they learned to their lives. This research was conducted by applying Classroom Action Research in two cycles, that is cycle I, and cycle II. Each of the cycle was done in four stages, namely plan, action, observation, and reflection. The instrument for collecting data was oral test. The problem was found in cycle I, some of students there still have difficulties in speaking and bored learn English. In cycle II, all students feel enjoy and happy, it means that they have an improving of their speaking. The subject of this study was one class in the eighth grade students of SMP Negeri 2 Siborongborong. There are 38 students that participated. The qualitative and quantitative data were gathered by administrating oral test and diary notes. The result of quantitave data obtained that the score of students improved from cycle I, and cycle II which the mean of the first cycle was 65.68, the second cycle was 80.97. The result of qualitative data described that the use of Role Play to improve the students’ speaking ability.